Battery diaphragm and preparation method thereof
By applying UV curing coating on polyolefin-based battery separator, combined with online coating and UV curing technology, the problem of insufficient mechanical strength at high temperatures is solved, significantly improving the performance and safety of the battery separator, and having production efficiency and Advantages of environmental protection.
Patent Information
- Application Number
- CN202411294599.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing polyolefin-based battery separators have insufficient mechanical strength under high temperature conditions, making it difficult to meet the needs of extreme use environments.
UV curing coatings including photoinitiators, solvents and nanozirconium dioxide are combined with polyolefin-based films. The mechanical strength of the film is improved through online coating and UV curing techniques, and the chemical bonding degree between the coating and the base film is increased. .
It significantly improves the thermal needle puncture strength, film rupture temperature and thermal shrinkage performance of the battery separator, improves the safety and performance of lithium-ion batteries, and also has the advantages of short production cycle and low energy consumption.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery separators, and in particular to a battery separator and a preparation method thereof. Background Art
[0002] As the current mainstream energy storage device, lithium-ion batteries are widely used in electric vehicles, portable electronic devices and other fields. Among them, the performance of the diaphragm, as one of the key components of the battery, directly affects the overall performance and safety of the battery. Polyolefin-based membranes have become one of the main materials for lithium-ion battery diaphragms due to their excellent chemical stability, good insulation and certain mechanical strength. However, with the continuous development of battery technology, higher requirements are placed on the mechanical strength of the diaphragm, especially in the face of challenges in extreme use environments. For example, under high temperature conditions, the mechanical strength of existing polyolefin-based membranes can no longer meet the requirements. Summary of the invention
[0003] The present invention provides a battery separator and a preparation method thereof, which solves the problem of poor strength of polyolefin-based battery separators at high temperatures in the related art.
[0004] The technical solution of the present invention is as follows: The present invention provides a battery separator, comprising a polyolefin base film and a UV-curable coating coated on at least one surface of the polyolefin base film; The UV curing coating comprises the following raw materials in parts by weight: 0.1-0.3 parts of a photoinitiator and 100 parts of a solvent; The photoinitiator includes one or more of 2-ethylanthraquinone, 4-chlorobenzophenone, 2,2-dimethoxy-1,2-diphenylalkane-1-one, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
[0005] As a further technical solution, the solvent includes one or more of ether, ethanol, isopropanol, acetone, and ethyl acetate; The polyolefin-based film comprises the following raw materials in parts by weight: 15 to 30 parts of polyolefin and 70 to 85 parts of diluent; The polyolefin includes polyethylene with a molecular weight of 600,000 to 1.2 million.
[0006] As a further technical solution, the diluent is mineral oil.
[0007] As a further technical solution, the photoinitiator includes 2-ethylanthraquinone, 4-chlorobenzophenone, and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 1:2:2 to 3:1:1.
[0008] In the present invention, when the photoinitiator uses 2-ethylanthraquinone, 4-chlorobenzophenone, and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 1:2:2 to 3:1:1, the strength of the polyolefin-based battery separator at high temperature is further improved.
[0009] As a further technical solution, the UV curing coating further comprises the following raw materials in parts by weight: 0.05 to 0.2 parts of nano zirconium dioxide; The polyolefin-based film further comprises the following raw materials in parts by weight: 5 to 10 parts of filler.
[0010] As a further technical solution, the filler includes nano silicon dioxide and nano zirconium dioxide in a mass ratio of 1:5 to 7:1.
[0011] In the present invention, nano silicon dioxide and nano zirconium dioxide are added as fillers in a mass ratio of 1:5 to 7:1 in the polyolefin-based film, and cooperate with the zirconium dioxide of the UV-cured coating to further improve the strength of the polyolefin-based battery separator at high temperatures.
[0012] As a further technical solution, the filler is a vinyl bisstearamide modified filler.
[0013] In the present invention, by using vinyl bisstearamide to modify the filler in the polyolefin-based film, the agglomeration between the fillers is reduced, the compatibility with the polyolefin-based film is improved, and the strength of the polyolefin-based battery separator at high temperature is further improved.
[0014] As a further technical solution, the preparation method of the vinyl bisstearamide modified filler comprises the following steps: mixing vinyl bisstearamide and a filler to obtain the vinyl bisstearamide modified filler.
[0015] As a further technical solution, the mass ratio of the vinyl bisstearamide to the filler is 0.4~0.5:2.
[0016] The present invention also provides a method for preparing a battery separator, comprising the following steps: S1, mixing the raw materials of the UV curing coating to obtain a coating slurry; S2. The raw materials of the polyolefin-based film are mixed, extruded into a film, heat-set, and coated with the coating slurry online, UV-cured, and heat-set to obtain a battery separator.
[0017] As a further technical solution, the thickness of the UV-cured coating of the battery separator is 0.01-1.5 μm.
[0018] As a further technical solution, the online coating includes one of dip coating, micro gravure coating and wire rod coating.
[0019] The prepared coating material is evenly coated on the surface of the continuously running polyolefin base film through a precision coating device by combining online coating and UV curing. Subsequently, the coating is quickly cured using an efficient UV light source. The ultraviolet light emitted by the UV light source penetrates the coating, activates the photoinitiator, and triggers a series of cross-linking reactions, causing the coating to cure rapidly in a short time. During this process, a strong chemical bond is formed between the coating and the base film, significantly improving the bonding strength between the two.
[0020] The working principle and beneficial effects of the present invention are: In the present invention, a high-strength bond between the coating and the base film is achieved through a unique coating formula and UV curing, which effectively solves the shortcomings of traditional coating technology in improving mechanical strength and provides a new solution for improving the safety, durability and performance of lithium-ion batteries. The polyolefin base film of the online-coated UV curing coating technology shows significant improvements in thermal puncture strength, film rupture temperature and thermal shrinkage performance. Specifically, compared with the uncoated polyolefin base film, its thermal puncture strength can be increased by more than 30%, the film rupture temperature can be increased by more than 20%, and the thermal shrinkage performance is also significantly improved. And due to the high efficiency of the UV curing coating, the present invention also has the advantages of short production cycle and low energy consumption, and has a high value for promotion and application. DETAILED DESCRIPTION
[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] In the following examples and comparative examples, the particle size of nano zirconium dioxide is 10 nm; the particle size of nano silicon dioxide is 10 nm.
[0023] Example 1 A battery separator, comprising a polyolefin base film and a UV-cured coating with a thickness of 0.05 μm coated on the upper surface of the polyolefin base film; The UV curing coating includes the following raw materials in parts by weight: 0.3 parts of a photoinitiator and 100 parts of acetone; the photoinitiator is 2-ethylanthraquinone; The polyolefin-based film includes the following raw materials in parts by weight: 30 parts of polyethylene with a molecular weight of 600,000 and 70 parts of white oil; A method for preparing a battery separator comprises the following steps: S1, mixing raw materials of UV curing coating to obtain coating slurry; S2. The raw materials of the polyolefin-based film are mixed, extruded into a film, heat-set, and the above-mentioned coating slurry is applied online at a running speed of 40 m / min, UV-cured, and heat-set to obtain a battery separator.
[0024] Example 2 A battery separator, comprising a polyolefin base film and a UV-cured coating with a thickness of 0.03 μm coated on the upper surface of the polyolefin base film; The UV curing coating includes the following raw materials in parts by weight: 0.2 parts of a photoinitiator and 100 parts of acetone; the photoinitiator is 4-chlorobenzophenone; The polyolefin-based film includes the following raw materials in parts by weight: 20 parts of polyethylene with a molecular weight of 900,000 and 80 parts of white oil; A method for preparing a battery separator comprises the following steps: S1, mixing raw materials of UV curing coating to obtain coating slurry; S2. The raw materials of the polyolefin-based film are mixed, extruded into a film, heat-set, and the above-mentioned coating slurry is coated online at a running speed of 50 m / min, UV-cured, and heat-set to obtain a battery separator.
[0025] Example 3 A battery separator, comprising a polyolefin base film and a UV curing coating with a thickness of 0.01 μm coated on the upper and lower surfaces of the polyolefin base film; The UV curing coating includes the following raw materials in parts by weight: 0.1 parts of a photoinitiator and 100 parts of acetone; the photoinitiator is 2,2-dimethoxy-1,2-diphenylalkane-1-one; The polyolefin-based film includes the following raw materials in parts by weight: 15 parts of polyethylene with a molecular weight of 1.2 million and 85 parts of white oil; A method for preparing a battery separator comprises the following steps: S1, mixing raw materials of UV curing coating to obtain coating slurry; S2. The raw materials of the polyolefin-based film are mixed, extruded into a film, heat-set, and the above-mentioned coating slurry is applied online at a running speed of 60 m / min, UV-cured, and heat-set to obtain a battery separator.
[0026] Example 4 The only difference between this embodiment and embodiment 1 is that the photoinitiator is 4-chlorobenzophenone and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 1:1.
[0027] Example 5 The only difference between this embodiment and embodiment 1 is that the photoinitiator is 2-ethylanthraquinone and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 3:1.
[0028] Example 6 The only difference between this embodiment and embodiment 1 is that the photoinitiator is 2-ethylanthraquinone and 4-chlorobenzophenone in a mass ratio of 3:1.
[0029] Example 7 The only difference between this embodiment and embodiment 1 is that the photoinitiator is 2-ethylanthraquinone, 4-chlorobenzophenone, and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 3:1:1.
[0030] Example 8 The only difference between this embodiment and embodiment 1 is that the photoinitiator is 2-ethylanthraquinone, 4-chlorobenzophenone, and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 1:2:2.
[0031] Example 9 The only difference between this embodiment and embodiment 8 is that the UV curing coating further includes the following raw materials in parts by weight: 0.05 parts of nano zirconium dioxide.
[0032] Example 10 The only difference between this embodiment and embodiment 8 is that the UV curing coating further includes the following raw materials in parts by weight: 0.2 parts of nano zirconium dioxide.
[0033] Embodiment 11 The only difference between this embodiment and embodiment 8 is that the polyolefin-based film further includes the following raw materials in parts by weight: 5 parts of filler, which is nano-silicon dioxide and nano-zirconium dioxide in a mass ratio of 1:5.
[0034] Example 12 The only difference between this embodiment and embodiment 10 is that the polyolefin-based film further includes the following raw materials in parts by weight: 5 parts of filler, which is nano-silicon dioxide and nano-zirconium dioxide in a mass ratio of 1:5.
[0035] Embodiment 13 The only difference between this embodiment and embodiment 10 is that the polyolefin-based film further includes the following raw materials in parts by weight: 5 parts of filler, which is nano-silicon dioxide and nano-zirconium dioxide in a mass ratio of 7:1.
[0036] Embodiment 14 The only difference between this embodiment and Example 13 is that the filler is also modified with vinyl bisstearamide. The preparation method of the vinyl bisstearamide modified filler includes the following steps: mixing vinyl bisstearamide, filler and chloroform, and drying to obtain a vinyl bisstearamide modified filler; the mass ratio of vinyl bisstearamide and filler is 0.2:1, and the mass volume ratio of vinyl bisstearamide and chloroform is 1:30mL.
[0037] Embodiment 15 The only difference between this embodiment and Embodiment 13 is that the filler is a vinyl bisstearamide modified filler, and the preparation method of the vinyl bisstearamide modified filler comprises the following steps: vinyl bisstearamide, filler, and chloroform are mixed and dried to obtain a vinyl bisstearamide modified filler; the mass ratio of vinyl bisstearamide and filler is 0.5:2, and the mass volume ratio of vinyl bisstearamide and chloroform is 1:30mL.
[0038] Example 16 The only difference between this embodiment and embodiment 15 is that the thickness of the UV-cured coating is 1.5 μm; and the weight portion of the filler in the polyolefin-based film is 10 parts.
[0039] Comparative Example 1 This comparative example differs from Example 1 only in that the battery separator does not include a UV-curable coating.
[0040] Comparative Example 2 This comparative example differs from Example 2 only in that the battery separator does not include a UV-curable coating.
[0041] Comparative Example 3 This comparative example differs from Example 3 only in that the battery separator does not include a UV-curable coating.
[0042] The battery separators prepared in Examples 1 to 16 and Comparative Examples 1 to 3 were respectively subjected to the following performance tests: Hot needle puncture strength: Use a needle with a diameter of 1 mm and a tip bending radius of 0.5 mm to puncture the battery separator at a speed of 2 mm / sec, and measure the hot needle puncture strength of the maximum load value during puncture at different temperatures; Membrane rupture test: TMA method is used to test membrane rupture temperature and membrane rupture time; Shrinkage rate: The battery separator was placed in a 130°C oven for 1 hour in its natural state, and then the transverse (TD) shrinkage rate and longitudinal (MD) shrinkage rate of the battery separator were measured; The results are shown in Tables 1~2 below.
[0043] Table 1 Battery separator performance test results
[0044] By comparing Examples 1 to 3 and Comparative Examples 1 to 3, it is found that compared with Comparative Examples 1 to 3, the battery separators prepared in Examples 1 to 3 have higher hot needle puncture strength and ink splashing temperature and lower shrinkage rate, indicating that by combining online coating with UV curing and using an efficient UV light source to quickly cure the coating, a strong chemical bond is formed between the coating and the base film, which significantly improves the performance of the battery separator at high temperatures.
[0045] Table 2 Battery separator performance test results
[0046] By comparing the data of Example 1 and Examples 4 to 8, it is found that compared with Example 1 and Examples 4 to 6, the hot needle puncture strength of the battery separators prepared in Examples 7 to 8 is higher, indicating that when the photoinitiator uses 2-ethylanthraquinone, 4-chlorobenzophenone, and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 1:2:2 to 3:1:1, the strength of the polyolefin-based battery separator at high temperature can be further improved.
[0047] By comparing the data of Examples 8 to 13, it was found that compared with Examples 8 to 11, the hot needle puncture strength of the battery separators prepared in Examples 12 to 13 was higher, indicating that nano-silicon dioxide and nano-zirconium dioxide were added as fillers in a mass ratio of 1:5 to 7:1 in the polyolefin-based film, and synergistically with the zirconium dioxide of the UV-cured coating, further improving the strength of the polyolefin-based battery separator at high temperatures.
[0048] By comparing the data of Examples 13 to 16, it is found that compared with Example 13, the hot needle puncture strength of the battery separators prepared in Examples 14 to 16 is higher, indicating that the strength of the polyolefin-based battery separator at high temperature is further improved by using the filler in the polyolefin-based film modified by vinyl bisstearamide.
[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A battery separator, characterized in that: comprising a polyolefin base film and a UV curing coating coated on at least one surface of the polyolefin base film; The UV curing coating comprises the following raw materials in parts by weight: 0.1-0.3 parts of a photoinitiator and 100 parts of a solvent; The photoinitiator includes one or more of 2-ethylanthraquinone, 4-chlorobenzophenone, 2,2-dimethoxy-1,2-diphenylalkane-1-one, 2,4-diethylthioxanthone, 2-isopropylthioxanthone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.
2. A battery separator according to claim 1, characterized in that: The solvent includes one or more of ether, ethanol, isopropanol, acetone, and ethyl acetate; The polyolefin-based film comprises the following raw materials in parts by weight: 15 to 30 parts of polyolefin and 70 to 85 parts of diluent; The polyolefin includes polyethylene with a molecular weight of 600,000 to 1.2 million.
3. A battery separator according to claim 1, characterized in that: The photoinitiator includes 2-ethylanthraquinone, 4-chlorobenzophenone, and 2,2-dimethoxy-1,2-diphenylalkane-1-one in a mass ratio of 1:2:2 to 3:1:
1.
4. A battery separator and a method for preparing the same according to claim 1, characterized in that: The UV curing coating further comprises the following raw materials in parts by weight: 0.05-0.2 parts of nano zirconium dioxide; The polyolefin-based film further comprises the following raw materials in parts by weight: 5 to 10 parts of filler.
5. A battery separator and a method for preparing the same according to claim 4, characterized in that: The filler comprises nano silicon dioxide and nano zirconium dioxide in a mass ratio of 1:5 to 7:
1.
6. A battery separator and a method for preparing the same according to claim 4, characterized in that: The filler is a vinyl bisstearamide modified filler.
7. A battery separator and a method for preparing the same according to claim 6, characterized in that: The preparation method of the vinyl bisstearamide modified filler comprises the following steps: mixing vinyl bisstearamide and filler to obtain the vinyl bisstearamide modified filler.
8. A battery separator according to claim 7, characterized in that: The mass ratio of the vinyl bisstearamide to the filler is 0.4-0.5:
2.
9. The method for preparing a battery separator according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, mixing the raw materials of the UV curing coating to obtain a coating slurry; S2. The raw materials of the polyolefin-based film are mixed, extruded into a film, heat-set, and coated with the coating slurry online, UV-cured, and heat-set to obtain a battery separator.
10. The method for preparing a battery separator according to claim 9, characterized in that: The thickness of the UV-cured coating of the battery separator is 0.01-1.5 μm.
Citation Information
Patent Citations
Functional diaphragm and preparation method thereof
CN109524603A
Diaphragm coating liquid, preparation method thereof, diaphragm, preparation method of diaphragm, and secondary battery
CN109860483A
Anti-oxidation high-puncture-strength dry diaphragm and preparation method and application thereof
CN110165129A
Preparation method of ultraviolet curing modified polyolefin battery diaphragm
CN114243207A
Multilayer composite lithium ion battery diaphragm and preparation method thereof
CN115172986A